2012
DOI: 10.1002/dta.1413
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PPARδ agonists GW1516 and GW0742 and their metabolites in human urine

Abstract: Peroxisome proliferator-activated receptor-δ (PPARδ) agonists are the drug candidates with potential performance-enhancing properties, and therefore their illegitimate use in sports should be controlled. To simulate the metabolism of PPARδ agonist GW0742, in vitro reactions were performed which demonstrated that the main metabolic pathway is oxidation of the acyclic divalent sulfur to give the respective sulfoxide and sulfone. After being characterized by liquid chromatography-mass spectrometry (LC-MS), these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…In contrast to the rodent toxicity studies, 1,9,10 no significant adverse effects were reported in clinical studies, probably due to the considerably lower dose administered (up to 10 mg/kg/day) and shorter administration period (up to 12 weeks) 1 . In our study, considering the possible risk of carcinogenicity of GW1516, only a single low oral dose of 0.3 mg/kg (150 mg/horse) was administered to a thoroughbred mare with reference to a healthy volunteer study in which a single oral dose of 15 mg was administered 7 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the rodent toxicity studies, 1,9,10 no significant adverse effects were reported in clinical studies, probably due to the considerably lower dose administered (up to 10 mg/kg/day) and shorter administration period (up to 12 weeks) 1 . In our study, considering the possible risk of carcinogenicity of GW1516, only a single low oral dose of 0.3 mg/kg (150 mg/horse) was administered to a thoroughbred mare with reference to a healthy volunteer study in which a single oral dose of 15 mg was administered 7 …”
Section: Resultsmentioning
confidence: 99%
“…To control the misuse of GW1516 by human athletes, Thevis et al 5,6 reported the generation of two potential monitoring targets, namely GW1516 sulfoxide and sulfone (Figure 1), based on two in vitro studies. Sobolevsky et al later administered oral GW1516 to a healthy volunteer and confirmed the suitability and applicability of GW1516 sulfoxide and its sulfone for doping control 7 . For horses, only detection of GW1516 in hair was reported by Gray et al in 2018 15 .…”
Section: Introductionmentioning
confidence: 91%
“…The ratio of 6 to 5 is at least 3:1 and increases with time. Consequently, 6 is a suitable marker to identify abuse of 4 …”
Section: Sulfides → Sulfoxidesmentioning
confidence: 99%
“…Mitochondrial biogenesis was not observed using 16 in the absence of any exercise stimulus; however, concomitant training of the test animals resulted in a 60–75% increase in their endurance performance exhibiting a specific “endurance gene signature” . Consequently, PPARβ/δ agonists have been considered as prohibited substances in sport since 2008, and test methods led to a series of adverse analytical findings for GW1516 in the past, despite the fact that the drug development was discontinued in 2007 due to observed increased risks of cancer in animal studies. Further substances that reportedly act as PPARβ/δ agonists are GW0742 and L165041 (Table , Fig.…”
Section: Pparδ Agonistsmentioning
confidence: 99%